2008
DOI: 10.1158/1055-9965.epi-08-0109
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Second Primary Malignancies in Women with Breast Cancer Diagnosed at Young Age: A Population-Based Study in Taiwan

Abstract: Studies conducted in Western countries have reported excess risks for second primary malignancies after breast cancer. However, there is little documentation of ethnic differences in these excess risks. Asian women are characterized by younger age at diagnosis of breast cancer, but very few reports are available on the incidences and risks for second primary cancers in this region. Using population-based data from the Taiwan National Cancer Registry (TNCR) for the period 1979 to 2003, we quantified standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
87
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 43 publications
11
87
0
2
Order By: Relevance
“…For most of the cancer sites or groups of cancer sites, we found a decrease in risk by increasing age at breast cancer though the magnitude of decrease varied. We found a steep decrease in risk for ovarian cancer by age at breast cancer in accordance with earlier studies (3)(4)(5); deleterious mutations in the BRCA1 and BRCA2 genes predisposing to breast cancer and ovarian cancer are likely to be the underlying explanation for this observation (27).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For most of the cancer sites or groups of cancer sites, we found a decrease in risk by increasing age at breast cancer though the magnitude of decrease varied. We found a steep decrease in risk for ovarian cancer by age at breast cancer in accordance with earlier studies (3)(4)(5); deleterious mutations in the BRCA1 and BRCA2 genes predisposing to breast cancer and ovarian cancer are likely to be the underlying explanation for this observation (27).…”
Section: Discussionsupporting
confidence: 92%
“…We found a weak U-shaped relationship between age at breast cancer and risk of endometrial cancer consistent with some previous studies (3,4), whereas 1 study reported a clear increasing trend by increasing age (5). The increase in risk of endometrial cancer by age confined to older age groups is in contrast to the findings for most cancer sites, where risk decreased by age throughout the age spectrum or no trend by age was seen.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The classification of subtypes has been shown to provide prognostic information and etiologic mechanisms of breast cancer. In Taiwan, the young women breast cancer tends to be more luminal A type with higher ER and PR expression and less basallike subtype than that of the older women (Cheng et al, 2000;Lin et al, 2009), but with higher risk of second primary malignancy and worse prognosis (Lee et al, 2008;Mellemkjaer et al, 2006;Yu et al, 2006). This feature is quite distinct from that of western developed countries with high prevalence of more aggressive basal-like breast cancer in young women.…”
mentioning
confidence: 94%
“…Development of SPC is associated with poor survival (Lee et al, 2008;Schaapveld et al, 2008;Buchler et al, 2011), and screening for SPC is one of the key components of survivorship care (Cheung et al, 2009). Cancer screening can reduce the risk of dying from selected cancers through early detection, when the stage of cancer is more amenable to effective treatment (Shapiro et al, 1971;Timonen & Pyorala, 1977;Mandel et al, 1993).…”
Section: Introductionmentioning
confidence: 99%